All‐Dielectric Meta‐Reflectarray for Efficient Control of Visible Light. Issue 3 (7th December 2017) - Sun, Shang; Zhou, Zhenxing; Zhang, Chen; Yang, Wenhong; Song, Qinghai; Xiao, Shumin
Abstract: Wide‐bandgap material based all‐dielectric metasurfaces have been ideal platforms for the realization of arbitrary phase control in visible spectrum. While TiO2 metasurfaces are very promising in broadband and high‐efficiency anomalous transmission, meta‐hologram, and meta‐lenses et al., the current realizations are strongly dependent on the sophisticated fabrication technique to fabricate TiO2 nano‐pillars with aspect ratio > 10. Herein we experimentally demonstrate a much simpler approach to realize efficient phase control of visible light. By exploiting TiO2 nano‐blocks as meta‐atoms on a ground metal plane, we find that TiO2 metasurface with aspect ratio around 1‐1.5 is good enough to produce phase changes covering ‐π to π and high reflection efficiency simultaneously. Based on the phase control of the meta‐reflectarray, anomalous reflection with a ratio between anomalous reflection and normal reflection ∼ 74/26 have been experimentally realized using a combination of typical electron‐beam lithography, electron‐beam evaporation, and a simple lift‐off process. Similarly, high performance TiO2 metasurface in form of hologram has also been demonstrated for red (633 nm), green (520 nm), and blue (445 nm) wavelengths. We believe this research shall route a new way to cost‐effective all‐dielectric metasurfaces and advance their applications in encryption, anti‐counterfeiting, and wearable displays. Abstract : In our study, TiO2 nano‐blocks as meta‐atoms on a ground metal plane with aspect ratio around 1‐1.5 can provide efficient full phase control. Using a combination of typical electron‐beam lithography, electron‐beam evaporation, and a simple lift‐off process, high performance TiO2 metasurface in form of anomalous reflection and hologram has been demonstrated for visible wavelengths.